FRI0249 IN MYOSITIS PATIENTS, SJÖGREN'S SYNDROME IS ASSOCIATED WITH INCLUSION BODY MYOSITIS AND WITH ANTI-CN1A ANTIBODIES INDEPENDENTLY OF THE MYOSITIS SUBTYPE. (13th June 2020) - Levy, D.; Nespola, B.; Giannini, M.; Felten, R.; Varoquier, C.; Rinagel, M.; Korganow, A. S.; Poindron, V.; Martin, T.; Maurier, F.; Chereih, H.; Bouldoires, B.; et al.
Abstract : Background: Myositis are characterized by weakness and muscle inflammation. They encompass heterogeneous conditions, which include dermatomyositis (DM), inclusion body myositis (IBM) and polymyositis (PM) according to the EULAR/ACR 2017 criteria. We recently recorded a high prevalence of IBM in a cohort of primary Sjögren's syndrome (SS) (1). The signification of SS in the setting of myositis is unanswered. Objectives: To refine the signification of SS in the setting of myositis. Methods: Among a monocentric myositis cohort (according to the EULAR/ACR 2017 criteria), SS patients (according to the ACR/EULAR 2016 criteria) were identified (myositis/SS+ group) and compared to myositis patients without SS (myositis/SS- group). Results: Among 414 myositis patients, SS criteria were available for 96 patients. Thirty two (33%) presented SS. Patients with SS tended to be more frequently women (F/M ratio 9.7 vs 3.0, p = 0.07). Age at diagnosis of myositis was similar in both groups (53 years [range 21-74] vs 53 years [range 16-77], p = 0.51). Myositis subtypes repartition (as defined by EULAR/ACR 2017 criteria) was different in myositis/SS+ and myositis/SS- groups (p = 0.021), IBM being four-fold more prevalent in myositis/SS+ group (25% vs 6%, p = 0.018). Accordingly, the delay between the first muscle symptoms and myositis diagnosis was longer in myositis/SS+ group (7 months [0-336] vs 4 months [0-122], p = 0.041). Moreover, aside anti-cN1A antibodies, myositis-specific antibodies were less frequently found in myositis/SS+ patients than in myositis/SS- ones (16/32 [50%] vs 46/64 [72%], p = 0.035). Anti-cN1A antibodies were more prevalent in myositis/SS+ patients (33% vs 5.8%, p = 0.0032). However, in myositis/SS+ group, anti-cN1A were frequent in each of the EULAR/ACR 2017 myositis subtypes and the association between SS and anti-cN1A positivity was maintained in a multivariate analysis adjusted with the diagnosis of IBM (p = 0.023). Seven of the myositis/SS+ patients (22%) had systemic involvement typical of SS (vs 6 [9%] of the myositis/SS- patients, p = 0.12) including polyneuropathy (6 [20%] vs 6 [10%]) and type 2 cryoglobulinaemic vasculitis (1 [3%] vs 1 [1.6%]). In addition, 2 (6%) myositis/SS+ patients developed a lymphoma (one B diffuse large cell lymphoma of the parotid and one non-Hodgkin lymphoma), vs none of the myositis/SS- patients (p = 0.11). Only one (3%) of the myositis/SS+ patients developed myositis-associated cancer (diagnosed within 3 years of myositis diagnosis) versus 6 (9%) of the myositis/SS- patients (p = 0.66). Aside hydroxychloroquine, more frequently used in myositis/SS+ group (38% vs 16%, p = 0.018), no significant difference was found in the management of the patients (taking into account the myositis subtype). Conclusion: Myositis patients with SS have more frequently IBM than myositis patients without SS. They also have more frequently anti-cN1A antibodies, independently of the myositis subtype. They might develop systemic complications of SS. References: [1]Felten R, Seror R, Vittecoq O, Hachulla E, Perdriger A, Dieude P, et al. SAT0470 Myositis, often suspected, is actually rare in primary Sjögren's syndrome: data from the French cohort ASSESS. In BMJ Publishing Group Ltd and European League Against Rheumatism; 2018. p. 1093.1–1093. Available from: http://ard.bmj.com/lookup/doi/10.1136/annrheumdis-2018-eular.2945 Disclosure of Interests: Dan LEVY: None declared, Benoit Nespola: None declared, Margherita Giannini: None declared, Renaud FELTEN: None declared, Coralie Varoquier: None declared, Marina Rinagel: None declared, Anne-Sophie Korganow: None declared, Vincent Poindron: None declared, Thierry Martin: None declared, Francois Maurier: None declared, Hassam Chereih: None declared, Bastien Bouldoires: None declared, Baptiste Hervier: None declared, Cédric Lenormand: None declared, Laurent Arnaud: None declared, Bernard Geny: None declared, Jean Sibilia: None declared, Jacques-Eric Gottenberg Grant/research support from: BMS, Pfizer, Consultant of: BMS, Sanofi-Genzyme, UCB, Speakers bureau: Abbvie, Eli Lilly and Co., Roche, Sanofi-Genzyme, UCB, alain meyer: None declared